Paradoks Kemuliaan dan Salib dalam Markus 10:45 terhadap Dinamika Kehidupan Spiritual Jemaat - Rinto Njurumbatu; Daniel Pesah Purwonugroho; Loudy Benedictus Pranatha (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2026)
This paper aims to examine the theology of the cross in Mark 10:45 in relation to the dynamics of the spiritual life of the congregation in order to provide a paradoxical perspective on glory and the cross. The theology of the cross is a theological perspective on the cross that elaborates on how God reveals himself through the suffering of the cross. The theology of the cross offers a critique of the paradigm of glory that has emerged in contemporary spirituality within the church. On the one hand, Mark 10:45 is a key text that elaborates on the identity of the Messiah in the context of sacrifice and the cross. This context is the path that Jesus took even though it contradicted the worldly understanding of glory and hope. Through qualitative literature research, the author will examine the theology of the cross in Mark 10:45 to elaborate a paradoxical understanding of glory and the cross that impacts the spiritual life of the congregation. The theology of the cross in Mark 10:45 provides a significant paradigm for shaping the life of the congregation to take part in the suffering of Christ. This paper offers an integrative reading of Mark 10:45 within the framework of the theology of the cross, which places the cross at the center of the formation of the congregation's spirituality. Abstrak Tulisan ini bertujuan untuk menelaah theologia crucis Markus 10:45 terhadap dinamika kehidupan spiritual jemaat untuk memberikan perspektif paradoksial kemuliaan dan salib. Theologia crucis merupakan perspektif teologis salib yang mengelaborasi cara Allah memperkenalkan diri melalui penderitaan salib. Theologia crucis memberikan kritik bagi paradigma kemuliaan yang muncul dalam dunia spiritualitas kontemporer di dalam gereja. Spiritualitas gereja masa kini memasuki era kontemporer yang menjauh dari esensi salib. Spiritualitas era kontemporer masa kini membawa orang percaya hanya menghayati kemuliaan diri tanpa memandang salib. Di satu sisi, Markus 10:45 merupakan teks kunci yang mengelaborasikan identitas Mesias dalam kerangka pengorbanan dan salib. Kerangka tersebut merupakan jalan yang Yesus tempuh meskipun berkontradiksi dengan pemahaman kemuliaan dan harapan duniawi. Melalui penelitian kualitatif studi pustaka, penulis akan menelaah theologia crucis Markus 10:45 untuk mengelaborasikan sebuah pemahaman paradoksial kemuliaan dan salib yang berdampak bagi kehidupan spiritual jemaat. Theologia crucis Markus 10:45 memberikan paradigma yang signifikan untuk membentuk kehidupan jemaat agar mengambil bagian dalam penderitaan Kristus. Tulisan ini menawarkan pembacaan integratif Markus 10:45 dalam kerangka theologia crucis yang menempatkan salib sebagai pusat pembentukan spiritualitas jemaat.